The impact of the COVID‐19 pandemic on patients with chronic liver disease: Results from the Global Liver Registry. Issue 10 (26th July 2022) - Younossi, Zobair M.; Yilmaz, Yusuf; El‐Kassas, Mohamed; Duseja, Ajay; Hamid, Saeed; Esmat, Gamal; Méndez‐Sánchez, Nahum; Chan, Wah Kheong; Singal, Ashwani K.; Lam, Brian; Felix, Sean; Younossi, Elena; et al.
Abstract: Patients with preexisting chronic liver disease (CLD) may experience a substantial burden from both coronavirus 2019 (COVID‐19) infection and pandemic‐related life disruption. We assessed the impact of the COVID‐19 pandemic on patients with CLD. Patients enrolled in our Global Liver Registry were invited to complete a COVID‐19 survey. As of June 2021, 2500 patients (mean age ± SD, 49 ± 13 years; 53% men) from seven countries completed the survey. Of all survey completers, 9.3% had COVID‐19. Of these patients, 19% were hospitalized, 13% needed oxygen support, but none required mechanical ventilation. Of all patients including those not infected with COVID‐19, 11.3% reported that the pandemic had an impact on their liver disease, with 73% of those reporting delays in follow‐up care. The Life Disruption Event Perception questionnaire confirmed worsening in at least one area (food/nutrition, exercise, social life, vocation/education, financial situation, housing, or health care) in 81% and 69% of patients with and without a history of COVID‐19, respectively ( p = 0.0001). On a self‐assessed Likert health score scale (range, 1–10; 10 indicates perfect health), patients with a COVID‐19 history scored lower (mean ± SD, 6.7 ± 2.2 vs. 7.4 ± 2.2, respectively; p < 0.0001) despite reporting similar health scores if there was no pandemic (mean ± SD, 8.5 ± 1.4 vs. 8.4 ± 1.6, respectively; p = 0.59). After adjustment for country of enrollment, liver disease etiology and severity, age, sex, body mass index, diabetes, and history of psychiatric comorbidities, COVID‐19 was found to be independently associated with lower self‐assessed health scores (beta = −0.71 ± 0.14; p < 0.0001). The COVID‐19 pandemic resulted in a substantial burden on the daily life of patients with CLD. Abstract : image